2022
DOI: 10.3390/agriculture12121996
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Humic Acid Urea Improves Nitrogen Use Efficiency and Crop Yield by Reducing the Nitrogen Loss Compared with Urea

Abstract: Enhancing nitrogen (N) use efficiency (NUE) and reducing urea N losses are major challenges in ensuring sustainable agriculture. The aim of this study was to investigate the effect of humic acid urea on N losses, soil microbial nutrient balance and NUE through leaching experiments, soil incubation experiments and field experiments of maize-wheat rotation. We set up four N gradients (240 kg N hm−2, 216 kg N hm−2, 192 kg N hm−2, 168 kg N hm−2) and two N fertilizer types (urea and humic acid urea) to make up five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…N is indispensable for the development of modern agriculture in China, and many studies have been performed to explore the positive effects induced by FA application on plant NUE. Similar to the results obtained by Kong et al [12] in which humic acid (HA) application reduced N loss, authors such as Gao et al [9] also reported that FA application could efficiently reduce ammonia volatilization from urea by inhibiting urease activity, and the formation of stable FA urea complexes under the combined application of FA and urea could also delay urea decomposition. Due to regulations, the goal of N preservation and N loss reduction has been achieved, which not only minimizes adverse environmental effects but is also beneficial in improving plant NUE.…”
Section: Introductionsupporting
confidence: 69%
“…N is indispensable for the development of modern agriculture in China, and many studies have been performed to explore the positive effects induced by FA application on plant NUE. Similar to the results obtained by Kong et al [12] in which humic acid (HA) application reduced N loss, authors such as Gao et al [9] also reported that FA application could efficiently reduce ammonia volatilization from urea by inhibiting urease activity, and the formation of stable FA urea complexes under the combined application of FA and urea could also delay urea decomposition. Due to regulations, the goal of N preservation and N loss reduction has been achieved, which not only minimizes adverse environmental effects but is also beneficial in improving plant NUE.…”
Section: Introductionsupporting
confidence: 69%
“…The higher total soil N availability in rhizosphere found in humalite treated plants could be due to reduced N losses from leaching or N 2 O emissions as HPs are known to reduce N losses. Kong et al (2022) found that the application of HAtreated urea reduced the N losses from leaching and N 2 O emissions by 25.5% and 23%, respectively, in laboratory experiments performed using field soil. The authors found that HA-treated urea increased the NUE of maize and wheat by 35.3% and 77.5% and yield by 14.2% and 15.5%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Kong et al. (2022) found that the application of HA‐treated urea reduced the N losses from leaching and N 2 O emissions by 25.5% and 23%, respectively, in laboratory experiments performed using field soil. The authors found that HA‐treated urea increased the NUE of maize and wheat by 35.3% and 77.5% and yield by 14.2% and 15.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment from humic acid with micronutrients gave higher results. Humic acid will reduce N losses in soil by around 23-25% from leaching, NH3 volatilization, and N2O emission (Kong et al, 2022). The available P in control was zero but its level significantly increased with both humic acid treatments.…”
Section: Chemical Characteristics Of Soilmentioning
confidence: 97%